2018
DOI: 10.22454/fammed.2018.936023
|View full text |Cite
|
Sign up to set email alerts
|

Testing Quick Response (QR) Codes as an Innovation to Improve Feedback Among Geographically-Separated Clerkship Sites

Abstract: Background and Objectives: Collection of feedback regarding medical student clinical experiences for formative or summative purposes remains a challenge across clinical settings. The purpose of this study was to determine whether the use of a quick response (QR) code-linked online feedback form improves the frequency and efficiency of rater feedback. Methods: In 2016, we compared paper-based feedback forms, an online feedback form, and a QR code-linked online feedback form at 15 family medicine clerkship sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…United States to online or paper alternatives [40]. It was found that the QR feedback forms were associated with the highest usability score and took the shortest amount of time to prepare by students.…”
Section: Snyder Et Al Compared the Use Of Qr Feedback Forms At 15 Fammentioning
confidence: 98%
See 1 more Smart Citation
“…United States to online or paper alternatives [40]. It was found that the QR feedback forms were associated with the highest usability score and took the shortest amount of time to prepare by students.…”
Section: Snyder Et Al Compared the Use Of Qr Feedback Forms At 15 Fammentioning
confidence: 98%
“…Four articles explore how QR codes can be used to improve trainee experience, either through improvement in feedback methods [39][40][41] or by recording procedures undertaken in a log book [42].…”
Section: Theme 4: Training Supportmentioning
confidence: 99%
“…As PGY-3 family medicine residents who both receive faculty feedback and are responsible for evaluating medical student performance, we read your recent article, "Testing Quick Response (QR) Codes as an Innovation to Improve Feedback Among Geographically-Separated Clerkship Sites" with great interest. 1 We commend the authors on highlighting a technology that could significantly improve the timeliness of student feedback while reducing the administrative burden required to do so. We believe that if properly implemented, such a system could be used to share feedback to learners in near real time.…”
Section: To the Editormentioning
confidence: 99%
“…We would like to thank Drs Barnes and Nowakowski for their comments on our recently published paper on the use of QR codes to promote timely feedback. 1 As they noted, timely, specific, and actionable feedback is critical in education, especially during short or highly demanding medical rotations. We believe QR technology provides a viable bridge to improve the communication between preceptor and learner.…”
Section: To the Editormentioning
confidence: 99%
“…Several small studies at academic teaching hospitals have found that QR readers used for trainee evaluations are associated with improved usability and more timely feedback. 4,5 QR codes also can be integrated into print or online publications. When embedded into journal articles or textbook chapters, they can link to resources that are less effectively modeled in fixed 2-dimensional figures.…”
mentioning
confidence: 99%